Perspectives on Using Artificial Intelligence in English Language Learning for Islamic Primary Teacher Education (PGMI) Students, Indonesia - Fitri Annisa (Universitas Islam Negeri Mataram, Indonesia, 2025)
The progression of artificial intelligence (AI) has significantly influence higher education. Even though AI tools (Chat GPT, google translate) gives advantages in vocabulary improvement, grammar checking, and independent learning but plagiarism, accuracy and technology addiction is become the core problem issue. This study aimed to explore the perspectives of students in the Madrasah Ibtidaiyah. Teacher Education Program (PGMI) at Institute Agama Islam Latifah Mubarrokiyah (IAILM) on the utilization of AI in English learning. This study used a mixed method design, analyzed quantitatively with descriptive statistics and qualitatively using thematic analysis. Stratified sampling techniques was used to gain sample which amount 44 students across four semesters. Questionnaire with closed and open ended questions were used to collect the data. Closed data item were measured using Likert Scale. The findings reveal that students have basic awareness and surface level experience with AI, mainly using it for vocabulary, translation, and grammar support. In terms of views and attitudes toward AI were moderately positive. It recognizes that the role of AI support language skills and creativity but it can be replaced the role of teachers. In the terms of concerns were also note, especially about plagiarism, inaccurate information, technology addiction, uncritical thinking. Generally, students regards AI as a supportive rather than substitutive tool in language learning. This study highlights the need of conducting AI literacy training at PGMI, integrating technological knowledge with ethical considerations to encourage critical thinking. This findings have practical implications for curriculum design and digital literacy development, particularly in preparing future elementary teachers to integrate AI in English teaching effectively.